Penerapan Building Information Modeling (BIM) Menggunakan Software Autodesk Revit 2019 pada Pekerjaan Non Struktur (Studi Kasus : Gedung B Fakultas Ekonomi dan Bisnis Universitas Lampung) - reviana, reviana; Bayzoni, Bayzoni; Husni, Hasti Riakara; Siregar, Amril Maruf (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
Indonesia's development in the construction sector is progressing very rapidly. With the increasing number of developments in Indonesia, the scale and types of work projects in the field of civil engineering are also increasingly varied. In infrastructure development there needs to be a good system and management. This good system and management can be found in the implementation of Building Information Modeling (BIM) in project implementation. BIM is a process of generating and managing building data in 3D in its project cycle where it can help human limitations in managing data and managing large resources and complex work systems so that errors can be minimized and projects can be analyzed in more depth (Succar , 2008). The purpose of this study was to conduct a study on the use of Building Information Modeling (BIM) in non-structural modeling of Building B, Faculty of Economics and Business, University of Lampung using the Autodesk Revit 2019 software. From the results of the research conducted, non-structural modeling in the form of modeling windows, walls, ceramics , doors and ceilings can be done quickly and well. Then the results of the BoQ comparison between the conventional and Revit methods show a significant difference, this is shown in the difference in brick wall work of -3.91%, the comparison of plastering and plastering work of 6.61%, the difference in the calculation of tiles and bathroom ceilings respectively respectively 3.29% and 4.69%, this is due to differences in calculating the area of brick walls using the conventional method using Revit 2019.